Isolated Bilateral Macrostomia. Issue 6 (September 2018) - Pradhan, Rohan; Lin, Bojie; Pan, Xin-Yuan; Yin, Guo-Qian
Abstract : Abstract: Macrostomia (Tessier's 7 cleft) is a rare congenital lip deformity. Macrostomia can occur unilateral or bilateral, isolated or associated with other syndromes. Isolated bilateral macrostomia is exceedingly rare with only a few cases reported to date. The authors report 6 cases of isolated bilateral macrostomia surgically repaired in 4-layered approaches. The traditional method was improved and the result obtained was satisfactory after longest follow-up of 3 years. The technique is easy to imitate, simple in design, aesthetically and functionally corrects the deformity.